Human papillomavirus vaccination in low- and middle-income countries: progression, barriers, and future prospective - Ebrahimi, Narges; Yousefi, Zahra; Khosravi, Gholamreza; Malayeri, Fatemeh Eskandari; Golabi, Marjan; Askarzadeh, Monireh; Shams, Mohammad Hossein; Ghezelbash, Behrooz; Eskandari, Nahid (Frontiers in Immunology, 2023)
Human papillomavirus (HPV) is a viral infection that, if does not go away, it can cause health problems like genital warts and cancer. The national immunization schedules for individuals before sexual debut, significantly decreased HPV-associated mortality and it will be affordable. However, immunization programs remain vulnerable to macroeconomic factors such as inflation, fiscal policy, employment levels and national income. The aim of this review is to investigate the association between national income in lower-middle-income countries to explore recent advances and potential issues, as well as how to deal with challenges.